PENGARUH MARKETING MIX TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA USAHA MIKRO - Juli Dwina Puspita Sari; Dhea Riswana (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2022)
This study aims to determine the effect of marketing mix (product, price, promotion and location) on purchasing decisions of customers in small business located in Langsa city, Aceh named the Say Story coffee shop. quantitative methods is used to process the primary data compiled through a questionnaire distributed to 50 customers (respondents) of the Say Story coffee shop in Langsa City. Non-probability sampling via accidental sampling is utilised in determining the respondents within this study. The results showed that the product, price, promotion, and location simultaneously affect purchasing decisions. The product partially has a positive and significant effect on purchasing decisions, the price partially has a negative and significant effect on purchasing decisions, promotion partially has a negative and significant effect on purchasing decisions and location partially has a positive and significant effect on purchasing decisions at the Say Story coffee shop.